Early Monsoon Time Local Flow Characteristics over the Hetauda Valley and its Implications - Acharya, S.; Neupane, S.; Shrestha, R.; Chapagain, C.; Acharya, P.; Maharjan, S.; Regmi, R. (Journal of Institute of Science and Technology, 2015)
The early monsoon time atmospheric transport processes over the Hetauda valley, the closest low-land that accommodates the third largest industrial district of Nepal, has been studied with the application of Weather Research and Forecasting (WRF) Modeling System initialized with NCEP meteorological and USGS terrain elevation and land-use data. The study reveals that the mixing layer over the Hetauda valley may evolve as much as 3 km above the surface during the afternoon time. The near surface atmosphere of the valley appears very weakly stratified even in the early morning time indicating that prevailing meteorology over the valley favors efficient dispersion of air pollutants. The study also reveals that the daytime upslope winds over the Hetauda valley and associated northern mountains effectively intrude into the Kathmandu valley enhancing the southwesterly and northwesterly wind system of the valley. Intrusion of local flows appears to be accompanied with the excitation of mountain waves and plain-to-plateau wind. Formation of lowlevel rotors over the Hetauda valley, excitation of mountain waves and the strong downdrafts over the southwestern part of the Kathmandu valley may put aircrafts into high risk. The pattern of local flow fields strongly suggest that the increase emissions over the Hetauda valley can have significant help to further deteriorate the already unhealthy air of Kathmandu. Journal of Institute of Science and Technology, 2014, 19(2): 109-117